Knight's 24-hour trainer : Microsoft SQL server 2008 integration services - Knight, Devin (Wrox, 2009)
"Welcome to the video portion of Knight's 24-Hour Trainer: Microsoft® SQL Server® 2008 Integration Services."--Resource description page.